Effect of Different Parameters on the Adsorption of Textile Dye Maxilon Blue GRL from Aqueous Solution by Using White Marble - M. Kadim Aljebori, Aseel; Noor Alshirifi, Abbas (Asian Journal of Chemistry, 2012)
The adsorption of textile dye (Basic Maxilon Blue GRL) from aqueous solution by white marble was studied. The effect of different experimental parameters such as shaking contact time, initial concentration of GRL "2-16 mg L-1", initial pH 3-10 of aqueous solution, adsorbent dose 0.25-2 g/100 mL and temperature 283 K-308 K on the adsorption of GRL were investigated. The applicability of adsorption isotherms to study the adsorption behaviour has also been analyzed by Langmuir and Freundlich isotherm models. They were used to illustrate the experimental isotherms and isotherm's constants. It was found Freundlich isotherm model fitted well the adsorption data compare with Langmuir model. The equilibrium time at normal pH was found 60 min, the pH of the dye solution on the range of 3 was found favourable for the removal of GRL, also the extent of adsorption found to decrease as the temperature increased. The thermodynamic parameters (DG, DH and DS) were calculated, (DG) was calculated from equilibrium constant and were explained in the mean of the chemical structure of the adsorbate. The concentration of dye was measured before and after adsorption by using UV-Visible spectrophotometer at 590 nm.